Platform economics : rhetoric and reality in the Sharing Economy - Codagnone, Cristiano; Karatzogianni, Athina; Matthews, Jacob, active 2018 (Bingley, U.K. : Emerald Publishing Limited, 2018)
Platform Economics tackles head on the rhetoric surrounding the so-called "sharing economy", which has muddied public debate and has contributed to a lack of policy and regulatory intervention. The book sheds light on the sharing economy debate by offering an in-depth analysis both of rhetoric employed by sharing economy actors, and by mapping key aspects of digital labour markets. The platform is discussed both as a source of innovation and growth and as a matter of policy concern over competition, tax collection, consumers' protection, privacy, and algorithms transparency, and the future of work. The authors show that actors in the sharing economy have not only used the narratives describing the initial phase of the sharing movement to their advantage, but have also succeeded in enlisting diffuse interests as their allies. The authors' research draws particular attention to the predicted advent of technological unemployment in conjunction with widespread concern over the robotisation of jobs. Advocating an inter-disciplinary approach in which economics, sociology, anthropology, legal studies, and rhetorical analysis converge, this text will prove invaluable to students, researchers and economists alike.
Prelims -- Introduction -- Chapter 1 Platform Economics and the Sharing Economy: A Primer -- Chapter 2 Rhetoric, Reality, Impacts and Regulation in Labour Intermediation Platforms -- Chapter 3 Digital Labour Markets in a Broader Perspective -- Chapter 4 Ideological Production in Digital Intermediation Platforms -- Chapter 5 Conclusions and Research Agenda for the Future -- References -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Cooperation; Business & Economics -- Corporate Governance; Economics, finance, business & management